The Effect of Lactobacillus Acidophilus Microcapsule Which Encapsulated by Kappa Caragenan Toward in Vivo Functional Test - Dwi Setijawati; Muhammad Firdaus; Kartikaningsih Kartikaningsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2014)
The effect of Lactobacillus acidophilus microcapsule which encapsulated by kappa-caragenan toward in vivo functional test has been carried out. The goal were to get the viability of L. acidophilus and E. coli in the stool test animals which fed by L. acidophilus encapsulated kappa-caragenan, to get anti-cholesterol ability in feces test animals which fed by L. acidophilus encapsulated kappa- caragenan, gain the ability to decrease the activity of b - glukoronidase found in feces test animals by administration of L. acidophilus which encapsulated by kappa-carrageenan, get the ability of L. Acidophilus which encapsulated by kappa-carrageenan as an inducer of IgA obtained from stool test animals. Conclusion were the administration L. acidophilus encapsulated by kappa- caragenan may improve the viability of L. acidophilus and E. coli feces of mice and can raise cholesterol levels feces of mice and decrease the activity of b - glukoronidase feces of mice and increase levels of fecal IgA mice.